Unpacking Writing Needs of Nepalese University Students - Pandey, Gopal Prasad (International Journal of Language and Literary Studies, 2020)
Assessing students’ needs is an integral part of English for specific purposes (ESP) syllabus design. Due to the significance of writing in English for business-specific purposes, there has been increasing interest in ESP studies to assess students’ writing needs. This study aimed at exploring the writing needs of Bachelor of Business Studies students of Tribhuvan University (TU), Kathmandu, Nepal. Ninety-two Bachelor of Business Studies (BBS) first year students and ten English teachers of TU took part in this study. Questionnaires served as the main tools for conducting needs analysis (NA). The findings revealed that both the groups of participants (students and teachers) perceived all seven subskills of writing as ‘important’. There is consistency between students’ perceptions of the importance of subskills of writing and teachers’ perceptions of the importance of the subskills. Regarding the perceived competence, teacher participants found their students’ abilities to be “not very good” or even “poor” in the subskills which they considered ‘important’ or ‘very important’. They rated their students at levels lower than the ones students did. Students were rated poor at the following subskills of writing: reports, memos, agendas, notices, instruction booklets, user manuals, company brochures, letters and diaries, and messages. Findings indicated that ESP teachers are required to help students learn all the subskills of writing so that they can communicate in the target situations effectively.